PENGARUH TEMPERATUR CETAKAN PADA CACAT VISUAL PRODUK PISTON DENGAN METODE DIE CASTING - Aang Kurniawan; Susilo Adi Widyanto; Yusuf Umardhani (JURNAL TEKNIK MESIN, 2013)
The need of the piston is increasing with the increasing number of motorcycles. Piston are not only made by large scale producers but also by small and medium industries. Challenges faced by small and medium industries are how to compete with large industry due to limited knowledge and technology in the field of metal casting. The material used is secondhand aluminum and addition aluminum alloy ADC12 which is a composition of silicon <12%. The research is done with making mould of die casting and making of moulding machine. Variable selected in this research is die temperatur (250°C, 320oC, 350ºC and 400 oC) and cast temperatur is 800ºC which pass trough casting process with method of die casting to know the casting defect that happen analysed visually. Preparation of casting by melting secondhand aluminum and ADC12 whice later to process casting. Results show the casting defects that happened for example cold shut, shrinkage, rough surface and porosity. Optimum die temperatur in process casting piston product with metode of die casting is die temperatur 320ºC, because this temperatur defect that happened in the from of shrinkage happened some of just small at area below cover rough surface that happened of piston products that can still be tolerated. At die temperatur more than 320ºC the dominant shrinkage happened at the bottom of the piston cover. And the die temperatur less than 320ºC cold shut will happened primarily in the location of thin walled.